Introducing nerve-sparing approach during minimally invasive radical hysterectomy for locally-advanced cervical cancer: A multi-institutional experience. Issue 11 (November 2017) - Raspagliesi, Francesco; Bogani, Giorgio; Spinillo, Arsenio; Ditto, Antonino; Bogliolo, Stefano; Casarin, Jvan; Leone Roberti Maggiore, Umberto; Martinelli, Fabio; Signorelli, Mauro; Gardella, Barbara; Chiappa, Valentina; Scaffa, Cono; et al.
Abstract: Objective: To evaluate the impact of nerve-sparing (NS) approach on outcomes of patients undergoing minimally invasive radical hysterectomy (MRH) for locally advanced stage cervical cancer (LACC). Methods: Data of consecutive patients undergoing minimally invasive surgery for LACC were retrospectively retrieved in a multi-institutional setting from 2009 to 2016. All patients included had minimally invasive class III radical hysterectomy (MRH or NS-MRH). Propensity matching algorithm was used to decrease possible allocation bias when comparing outcomes between groups. Results: Overall, 83 patients were included. The prevalence of patients undergoing NS approach increased aver the study period (from 7% in the year 2009–2010 to 97% in the year 2015–2016; p-for-trend < 0.001). NS-MRH and MRH were performed in 47 (57%) and 36 (43%) patients, respectively. After the application the propensity-matching algorithm, we compared 35 patients' pair (total 70 patients). Postoperative complications rate was similar between groups. Patients undergoing NS-LRH experienced shorter hospital stay than patients undergoing LRH (3.6 vs. 5.0 days). 60-day pelvic floor dysfunction rates, including voiding, fecal and sexual alterations, were lower in the NS group in comparison to control group (p = 0.02). Five-year disease-free (p = 0.77) and overall (p = 0.36) survivals were similar comparing NS-MRH with MRH. Conclusions: The implementation of NS approach in the setting of LACC improves patients' outcomes, minimizing pelvic dysfunction rates. NS approach has not detrimental effects on survival outcomes.